Workplace and classroom incivility and learning engagement: the moderating role of locus of control - Ani Cahyadi (International Journal for Educational Integrity, 2021)
Abstract This study aims to examine the relationship between workplace and classroom incivility to learning engagement and the moderating role of internal locus of control in these relationships. An online questionnaire was administered to 432 students from three private universities in Jakarta, Indonesia. The regression analysis results showed that both workplace and classroom incivility has a negative and significant effect on learning engagement. In addition, the direct effect of workplace incivility on learning engagement is moderated by the locus of control. The negative effect of workplace incivility on learning engagement is stronger for students with low levels of internal locus of control than for those students with high levels of internal locus of control. This study provides a better understanding of the internal mechanism condition to reduce the negative effects of incivility experiences that occur in the workplace and classroom among student employees. The implications and limitations are also discussed.